Calculation of nonlinear vibrations of piecewise-linear systems using the shooting method - Khang, Nguyen Van; Cuong, Hoang Manh; Minh Tuan, Nguyen Thai (Vietnam Journal of Mechanics, 2012)
In this paper, an explicit formulation of the shooting scheme for computation of multiple periodic attractors of a harmonically excited oscillator which is asymmetric with both stiffness and viscous damping piecewise linearities is derived. The numerical simulation by the shooting method is compared with that by the incremental harmonic balance method (IHB method), which shows that the shooting method is in many respects distinctively advantageous over the incremental harmonic balance method.